ANALISIS SEKTOR BASIS DAN USAHATANI IKAN AIR TAWAR SEBAGAI KOMODITAS UNGGULAN DI KECAMATAN PAGELARAN KABUPATEN PRINGSEWU - Manalu, Brilian Patar Novenda; Affandi, Muhammad Irfan; Endaryanto, Teguh (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to analyze the base commodity and income levels of freshwater fish farmers. The research is conducted by survey method in which location was chosen purposively at Pagelaran and Lugusari Villages, Pagelaran Subdistrict of Pringsewu Regency with consideration that the location are the central of freshwater fish production (minapolitan areas). The samples are 44 freshwater fish farmers who are members of fish farmers group with farming experience of more than five years. The data was collected in June to July 2017 and is analyzed by Location Quotient (LQ) analysis to determine base commodity and fish farming analysis to identify income level of freshwater fish farmers. The result of LQ analysis and fish farming analysis showed that the main base commodity was goldfish with LQ score 1,18 and the highest income level from three business focus (breeding business, enlargement business, also the breeding and enlargement business of goldfish) was an enlargement business of goldfish with an income value of Rp1,556,440.29/1,000 m2/month. Key words: base sector, freshwater fish, goldfish, income, main commodity